Multifaceted intervention to enhance cognition in older people at risk of cognitive decline: study protocol for the Protein Omega-3 and Vitamin D Exercise Research (PONDER) study. Issue 5 (9th May 2019) - Macpherson, Helen; Brownell, Sarah; Duckham, Rachel L; Meyer, Barbara; Mirzaee, Sam; Daly, Robin M
Abstract : Introduction: An increasing number of people are living with cognitive impairment and dementia. Current pharmacological therapies at best reduce Alzheimer's disease symptomatology but do not delay dementia onset in those at high risk. Structured exercise interventions can enhance cognition in older people; however, to produce long lasting, clinically relevant cognitive benefits, it is proposed that a multifaceted approach incorporating exercise with dietary supplements will address a wider range of mechanisms involved in cognitive decline. The Protein Omega-3 aNd vitamin D Exercise Research (PONDER) study aims to investigate the cognitive effects of a multimodal exercise programme combined with nutritional supplementation in older adults with subjective memory impairment (SMI). Methods and analysis: The PONDER study is a single-centre, 12-month, community-based, parallel group, randomised, double-blind, placebo controlled trial involving a 6-month multifaceted intervention with a further 6-month follow-up. Participants will be 148 people from Melbourne, Australia, aged 60–85 years with SMI who will be randomised (1:1 ratio) to either a 6-month supervised multimodal exercise programme combined with omega-3 fatty acid, vitamin D and protein supplementation or a stretching/flexibility exercise programme combined with placebo supplements. The primary outcome is the change in cognition after 6 months as assessed by the Trail Making Test and global cognitive function assessed from the Cogstate Computerised battery. Secondary outcomes will include memory, working memory/learning and attention/psychomotor function, the Montreal Cognitive Assessment, mood, quality of life, muscle strength, physical function, body composition, cardiovascular health and sleep quality. Cognition at 12 months will represent a secondary outcome. Ethics and dissemination: This study has been approved by the Deakin University Human Research Ethics Committee (project 2016–260). Informed consent will be obtained from all participants. The authors intend to submit the findings of the study to peer-reviewed journals or academic conferences to be published. Trial registration number: ACTRN12616001549415; Pre-results.